Capillary ion chromatography with on-column focusing for ultra-trace analysis of methanesulfonate and inorganic anions in limited volume Antarctic ice core samples - Estrella Sanz Rodriguez; Samuel Poynter; Mark Curran; Paul Haddad; Robert Shellie; Nesterenko, PN; Brett Paull (2015)
Preservation of ionic species within Antarctic ice yields a unique proxy record of the Earth's climate his-tory. Studies have been focused until now on two proxies: the ionic components of sea salt aerosol and methanesulfonic acid. Measurement of the all of the major ionic species in ice core samples is typically carried out by ion chromatography. Former methods, whilst providing suitable detection limits, have been based upon off-column preconcentration techniques, requiring larger sample volumes, with potential for sample contamination and/or carryover. Here, a new capillary ion chromatography based analytical method has been developed for quantitative analysis of limited volume Antarctic ice core samples.The developed analytical protocol applies capillary ion chromatography (with suppressed conductivity detection) and direct on-column sample injection and focusing, thus eliminating the requirement for off-column sample preconcentration. This limits the total sample volume needed to 300 uL per analysis,allowing for triplicate sample analysis with <1 mL of sample. This new approach provides a reliable and robust analytical method for the simultaneous determination of organic and inorganic anions, including fluoride, methanesulfonate, chloride, sulfate and nitrate anions. Application to composite ice-core samples is demonstrated, with coupling of the capillary ion chromatograph to high resolution mass spectrometry used to confirm the presence and purity of the observed methanesulfonate peak.